The Effects of Analyst Following on Real Earnings Management: Evidence from Chinese Listed Companies - CEN, XIAOTAO (2020)
This study examines the impacts of analyst following on real earnings management by investigating Chinese listed companies from 2008 to 2019. Using multiple measurements of real earnings management and analyst following, we document that the firm followed by more analysts is significantly associated with lower level of real earnings management, where real earnings management is specifically presented by abnormal production costs, abnormal discretionary expenses, and abnormal cash flows from operations. Additionally, our findings indicate that given the number of covering analysts, experienced analysts are significantly and more negatively associated with real earnings management, where real earnings management is particularly measured by abnormal production costs. Meanwhile, we merely confirm a weak negative relationship between analyst industry specialization and real earnings management, and a weak negative (positive) relationship between female analyst participation (analyst education level) and real earnings management. In a word, this study provides empirical evidence for the constraining effects of analyst following on real earnings management. Keyword: Analyst Following, Analyst Coverage, Analyst Characteristics, Real Earnings Management